Seismic city : an environmental history of San Francisco's 1906 earthquake - Dyl, Joanna Leslie, 1973- (Weyerhaeuser environmental book., 2017)
"Seismic City argues that the disaster of 1906 must be understood as part of the ordinary relationship between the city and its natural surroundings. Despite its short-term drama and immediate impact on people's lives, the 1906 earthquake and fire did not transform the history of San Francisco. Instead, San Franciscans rapidly incorporated the crisis into pre-existing debates about urban ecology, urban development, and social relations in the city. In the modern era, Americans have generally viewed 'natural' disasters as anomalous, exceptional events. Interpreting disasters as unpredictable 'acts of nature' that represent a disruption of ordinary life has justified a failure to adequately plan for disasters and concealed the ways in which social factors such as poverty play as much of a role in causing disasters as the geological or meteorological events that precipitate crises. By applying these insights to a close study of San Francisco's 1906 earthquake, including the decades leading up to the disaster and the city's recovery in the years after 1906, this project demonstrates how disaster and recovery became integrated into San Francisco's history, rather than transforming the city, and makes an important contribution to the interdisciplinary field of natural disaster studies"--Provided by publisher.